2011
DOI: 10.1089/ten.tea.2010.0688
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Adipose Tissue from Uncultured Human Adipose Stromal Vascular Fraction on Collagen Matrix and Gelatin Sponge Scaffolds

Abstract: Adipogenic potential was evaluated in uncultured stromal vascular fraction (SVF) loaded onto porous 3D collagen matrix and gelatin sponge scaffolds with predefined shapes. The SVF was isolated from 16 freshly lipectomized fat. Mean cell number was 6.0±4.68×10(7) cells/mL, and mean cell viability was 72%. Flow cytometric analysis revealed adipose-derived stromal cells (CD31(-), CD34(-/+), CD45(-), CD90(+), CD105(-), CD146(-), and CD166(+)) in the SVF. Three hours after harvest of fat, 200  μL of isolated SVF wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…Our results were in line with those of another study that seeded hASCs onto electrospun PLA nanofiber [48]. Furthermore, prior studies have demonstrated that hASCs can grow and proliferate with various types of biomaterials [49][52]. Thus, hASCs can be considered a good cell type for a tissue engineering approach, as they are derived from an abundant and available source and can be harvested with minimal morbidity.…”
Section: Discussionsupporting
confidence: 90%
“…Our results were in line with those of another study that seeded hASCs onto electrospun PLA nanofiber [48]. Furthermore, prior studies have demonstrated that hASCs can grow and proliferate with various types of biomaterials [49][52]. Thus, hASCs can be considered a good cell type for a tissue engineering approach, as they are derived from an abundant and available source and can be harvested with minimal morbidity.…”
Section: Discussionsupporting
confidence: 90%
“…Second, the exact composition of the rat SVF was not examined in this study. However, it is likely that the cell elements in the SVF of the rat are comparable to those in human SVF [30]. Third, we have not determined whether the decreased fibrosis in the corpus cavernosum is the result of a direct interaction between ADSC and the extracellular matrix or whether this is the result of increased innervation of the corpus cavernosum.…”
Section: Discussionmentioning
confidence: 99%
“…For the in vivo study, gelatin sponge was used as scaffold material in adipose tissue engineering as reported elsewhere . Gelatin sponge (Nanjin Jinling Co., Nanjing, China) was punched into 2 × 2 × 0.25 cm 3 blocks under aseptic conditions.…”
Section: Methodsmentioning
confidence: 99%